Correction: Effects of nurse-led transitional care interventions for patients with heart failure on healthcare utilization: A meta-analysis of randomized controlled trials. - Minlu Li; Yuan Li; Qingtong Meng; Yinyin Li; Xiaomeng Tian; Ruixia Liu; Jinbo Fang (PLoS ONE, 2022)
[This corrects the article DOI: 10.1371/journal.pone.0261300.].